Identification and Mapping of a New Soybean Male-Sterile Gene, mst-M - Zhao, Qingsong; Tong, Ya; Yang, Chunyan; Yang, Yongqing; Zhang, Mengchen (Frontiers in Plant Science, 2019)
The use of sterility is common in plants and multiple loci for hybrid sterility have been identified in crops such as rice. In soybean, fine-mapping and research on the molecular mechanism of male sterility is limited. Here, we identified a male-sterile soybean line, which produces larger, abnormal pollen grains that stain poorly with I2-KI. In an inheritance test, all F1 plants were fertile and the F2 and F2:3 populations conformed with the expected segregation ratio of 3:1 (fertility:sterility) (p = 0.82) and showed a 1:2:0 ratio of homozygous fertile: heterozygous fertile: homozygous sterile genotypes (p = 0.73), suggesting that the sterility was controlled by a single recessive gene (designated “mst-M”). Bulked segregant analysis showed that almost all single-nucleotide polymorphisms (SNPs; 95.92%) were distributed on chromosome 13 and 868 SNPs (95.81%) were distributed in the physical region of Chromosome 13.21877872 to Chromosome 13.22862641. Genetic mapping revealed that mst-M was flanked by W1 and dCAPS-1 with genetic distances of 0.6 cM and 1.8 cM, respectively. The order of the consensus markers and known sterility genes was: Satt146 - (5.0 cM) - st5 - (2.5 cM) - Satt030 - (15.3 cM) - ms6 - (5.0 cM) - Satt149 - (39.5 cM) - W1 - (0.6 cM) - mst-M - (14.1 cM) - Satt516 (7.5 cM) - ms1 - (16.3 cM) - Satt595. These results suggest that mst-M is a newly identified male-sterility gene, which represents an alternative genetic resource for developing a hybrid seed production system for soybean.